Traffic jam of the undead. (American City & County, 2009)
The article reports that hackers have illegally programmed two electronic traffic signs on a busy stretch of road in Austin, Texas, in January 2009. According to Austin television station KXAN, the traffic signs display nonsense messages. Similar incidents have occurred in Illinois and Indiana. Austin Public Works spokesperson Sara Hartley condemned the incident.